ACCEPTANCE SYSTEM IN PROSPECTIVE EMPLOYEES CV.PRANATA GROUP - Ilham Indramulia; Ir. Irwan Bastian. MM Ir. Irwan Bastian. MM (Jurnal Sistem Informasi, 1996)
Labor is a factor which determines success or not a company, whether small firms orlarge companies, and if a company wants workers in accordance with the vacantposition, the company must also hold selectors first.Through this simple computer process it is hoped that a screening officer who takes along time can be done with appropriate calculations, quickly and carefully so that itcan be solved by time and plan yan g has been determined by the company.